2019
DOI: 10.1007/jhep04(2019)162
|View full text |Cite
|
Sign up to set email alerts
|

WIMP dark matter in the parity solution to the strong CP problem

Abstract: We extend the Standard Model (SM) with parity symmetry, motivated by the strong CP problem and dark matter. In our model, parity symmetry is conserved at high energy by introducing a mirror sector with the extra gauge symmetry, SU (2) R × U (1) R . The charges of SU (2) R × U (1) R are assigned to the mirror fields in the same way as in the SM, but the chiralities of the mirror fermions are opposite to respect the parity symmetry. The strong CP problem is resolved, since the mirror quarks are also charged unde… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 105 publications
(124 reference statements)
0
7
0
Order By: Relevance
“…ref. [29]. In the SU(2) L doublet vectorlike lepton case, we can find the allowed region where 1 TeV m X 3 TeV.…”
Section: Jhep08(2020)042mentioning
confidence: 81%
See 2 more Smart Citations
“…ref. [29]. In the SU(2) L doublet vectorlike lepton case, we can find the allowed region where 1 TeV m X 3 TeV.…”
Section: Jhep08(2020)042mentioning
confidence: 81%
“…As pointed out in ref. [29], allowing O(1%) fine-tuning between m X and m F , one should be able to find a narrow allowed region in this mass regime. In this paper, we do not focus on such a fine-tuned case.…”
Section: Jhep08(2020)042mentioning
confidence: 98%
See 1 more Smart Citation
“…The presence of the bidoublet field does not change this picture as it does not couple to quarks. Reference [71] demonstrated that integrating out the heavy mirror quarks does not generate phases for the SM quark Yukawas via RGE effects. So far we have only worked at tree-level.…”
Section: Strong Cp Problemmentioning
confidence: 99%
“…See also recent discussions[8][9][10][11][12] 2. The LR breaking effects from SUSY breaking should be sufficiently suppressed to solve the strong CP[17].…”
mentioning
confidence: 99%